Enhancing the efficacy of engraftment of cord blood for hematopoietic cell transplantation. Issue 3 (June 2016) - Broxmeyer, Hal E.
Abstract: Clinical cord blood (CB) hematopoietic cell transplantation (HCT) has progressed well since the initial successful CB HCT that saved the life of a young boy with Fanconi anemia. The recipient is alive and well now 28 years out since that first transplant with CB cells from his HLA-matched sister. CB HCT has now been used to treat over 35, 000 patients with various malignant and non-malignant disorders mainly using HLA-matched or partially HLA-disparate allogeneic CB cells. There are advantages and disadvantages to using CB for HCT compared to other sources of transplantable hematopoietic stem (HSC) and progenitor (HPC) cells. One disadvantage of the use of CB as a source of transplantable HSC and HPC is the limited number of these cells in a single CB collected, and slower time to neutrophil, platelet and immune cell recovery. This review describes current attempts to: increase the collection of HSC/HPC from CB, enhance the homing of the infused cells, ex-vivo expand numbers of collected HSC/HPC and increase production of the infused CB cells that reach the marrow. The ultimate goal is to manipulate efficiency and efficacy for safe and economical use of single unit CB HCT.